A Medical Hardware-Software System for Remote Monitoring of Heart Diseases - T. M. Magrupov; Z. M. Yuldashev; S. P. Abdihalikov (Известия высших учебных заведений России: Радиоэлектроника)
Introduction.  Wireless diagnostics of patients’  functional state is important  for ensuring timely detection and treatment of diseases. In this article, the development of a medical hardware-software system for remote monitoring of the state of biological objects is considered on the example of cardiovascular diseases.Aim. To develop a medical hardware-software system for remote monitoring of the main cardiovascular parameters and to expand the scope of medical remote telemetry equipment, which can eventually lead to improved medical services.Materials and methods.  On the example of cardiovascular diseases, an analysis of the existing medical hardwaresoftware system for remote monitoring of the state of biological objects was carried out, taking into account the cardiac monitoring of the electrocardiogram. This method is widely used for in the diagnostics and treatment of cardiovascular diseases.Results.  A  method  was proposed for creating  a  hardware-software  system  for  remote monitoring of the main cardiovascular parameters to ensure timely detection and treatment of diseases. The general structure of such a system, including its advantages and disadvantages and the routing of information, is described.  The proposed technology of  prolonged  remote monitoring of the patient's health state makes it possible to increase  the efficiency of detecting dangerous heartbeat arrhythmia by about 30%.Conclusions.  The  proposed system  solves  the  problem of registering biological parameters without significant interference in the patient’s vital  activity, which allows typical conditions to be traced. Remote data collection also facilitates the load on medical personnel, reduces the number of contacts with patients and improves their psychological state.